Fluvial CO2 and CH4 patterns across wildfire‐disturbed ecozones of subarctic Canada: Current status and implications for future change. (22nd January 2020) - Hutchins, Ryan H. S.; Tank, Suzanne E.; Olefeldt, David; Quinton, William L.; Spence, Christopher; Dion, Nicole; Estop‐Aragonés, Cristian; Mengistu, Samson G.
Abstract: Despite occupying a small fraction of the landscape, fluvial networks are disproportionately large emitters of CO2 and CH4, with the potential to offset terrestrial carbon sinks. Yet the extent of this offset remains uncertain, because current estimates of fluvial emissions often do not integrate beyond individual river reaches and over the entire fluvial network in complex landscapes. Here we studied broad patterns of concentrations and isotopic signatures of CO2 and CH4 in 50 streams in the western boreal biome of Canada, across an area of 250, 000 km 2 . Our study watersheds differ starkly in their geology (sedimentary and shield), permafrost extent (sporadic to extensive discontinuous) and land cover (large variability in lake and wetland extents). We also investigated the effect of wildfire, as half of our study streams drained watersheds affected by megafires that occurred 3 years prior. Similar to other boreal regions, we found that stream CO2 concentrations were primarily associated with greater terrestrial productivity and warmer climates, and decreased downstream within the fluvial network. No effects of recent wildfire, bedrock geology or land cover composition were found. The isotopic signatures suggested dominance of biogenic CO2 sources, despite dominant carbonate bedrock in parts of the study region. Fluvial CH4 concentrations had a high variability which could not be explained by any landscape factors. Estimated fluvial CO2 emissions were 0.63 (0.09–6.06, 95% CI) and 0.29 (0.17–0.44, 95% CI) g C m −2 year −1 at the landscape scale using a stream network modelling and a mass balance approach, respectively, a small but potentially important component of the landscape C balance. These fluvial CO2 emissions are lower than in other northern regions, likely due to a drier climate. Overall, our study suggests that fluvial CO2 emissions are unlikely to be sensitive to altered fire regimes, but that warming and permafrost thaw will increase emissions significantly. Abstract : We found that stream CO2 concentrations were primarily associated with greater terrestrial productivity and warmer climates, and decreased downstream the fluvial network. The isotopic 13 C signatures of CO2 suggested dominance of biogenic sources, despite carbonate bedrock in parts of the study region. Network scale CO2 concentrations and isotopes reflect degassing from soil respiration with the largest rivers never reaching equilibrium with the atmosphere.